The Strengbach Catchment: A Multidisciplinary Environmental Sentry for 30 Years. Issue 1 (20th December 2018) - Pierret, Marie-Claire; Cotel, Solenn; Ackerer, Philippe; Beaulieu, Emilie; Benarioumlil, Sylvain; Boucher, Marie; Boutin, René; Chabaux, François; Delay, Frederick; Fourtet, Colin; Friedmann, Pascal; Fritz, Bertrand; et al.
Abstract : Core Ideas: We present a general overview of research performed at the Strengbach catchment. Multidisciplinary studies are performed to understand export of water and associated fluxes. Long‐term data study disturbances such as acid rain, forest management, and climate change. Research activity associated with various observations at the Strengbach catchment in the Vosges Massif (880–1150 m) addresses many questions in the domains of hydrology and geochemistry. The catchment is the observation and experimental site of the Observatoire Hydro‐Géochimique de l'Environnement appointed by the Centre National de la Recherche Scientifique. It also belongs to the research facilities that form the French Network of Critical Zone Observatories (OZCAR), which supports a network of critical zone observatories. The catchment is small (0.8 km 2 ) with steep slopes (20–30%) on granitic bedrock that mainly allow for forestry (spruce and beech stands) as the main land cover. Meteorological, hydrological, and geochemical data have been monitored since 1986. The first studies conducted were dedicated to the elucidation of acid rain effects on forest ecosystems and particularly on forest decline. Multidisciplinary research studies conducted on the Strengbach catchment enable exploration of the following issues: (i) hydrological functioning at the scale of a small catchment and questions regarding the evolution and preservation of the water resources in mountainous environments (stock, recharge, infiltration, and water pathways), (ii) exchange processes observed at the soil–plant–atmosphere continuum and in particular weathering processes and the evolution of soil mineral fertility (Ca, Mg, K, P), (iii) processes responsible for the export of water and for associated fluxes (dissolved chemicals, suspended materials, bed loads) and their dynamic at the outlet, and (iv) responses of the ecosystems to environmental disturbances (acid rain, forest management, and climate change) and their current and future modeling.